Analysis of Learning Strategy Encourage Writing Skill by using ICT in Fifth Semester of Universitas Muhammadiyah Bengkulu - Safitri, Washurachim; Nurcholis, Ivan Achmad; Maryansyah, Yupika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The objective of the research was to find out the Learning strategies Encourage Writing Ability by using ICT in Fifth Semester of Universitas Muhammadiyah Bengkulu. There are many multimedia tools out there for student to use in learning specially in writing. Using ICT will help learning activity from teacher dominated to student centered. It has positive activity to achieve student mastery in writing ability. The design of this research was descriptive method. The instruments of the research were questionnaire and interview guidelines. The questionnaire has been distributed to 30 students in fifth semester. The results of the research showed that there were many student have strategies encourage their writing skill by using different types of ICT. Thus, it can make the process writing easier and fun for students. By this research, the student can get the opportunities to improve their skill and capable to applicate in some tools. Key words: ICT, Learning Strategies, Writing Skill